Introduction to quantum mechanics - Sengupta, Krishnendu; Pal, Palash B. (Cambridge: Cambridge University Press, 2023)
"Quantum mechanics is a subfield of physics that studies how the universe works at atomic and subatomic levels. It is an essential part of undergraduate and graduate courses in physics and undergraduate engineering courses in India. This book comes from the desk of authors who have decades of graduate-level teaching experience in quantum mechanics. It covers the syllabus requirements set forth by the University Grants Commission (UGC), India, and has additional several unique features that will set it apart. It introduces the students to vector space in the beginning to give a comprehensive idea of the mathematics involved in the concepts, has separate appendices emphasizing the techniques of differential equations, and covers applications of quantum mechanics related to atomic physics, condensed matter physics, particle physics, and so on. The text is carefully designed and is not completely mathematical; it gives equal emphasis to the discussions around physics and creates a nice balance. The book will be suitable for both undergraduate and graduate students taking courses in physics and chemistry. Several advanced topics have been covered in this book. They are expected to be beneficial particularly to graduate students and researchers"--
Includes bibliographical references and index.
Keywords: Quantum theory -- Textbooks; Quantum theory -- Mathematics -- Textbooks